Is Thrombocytopenia Consistent with Specific Bacterial/Fungal Neonatal Sepsis? - Javaid, Sulman; Waheed, Khawaja Irfan Ahmad; Sheikh, Mehmood; Gul, Rafia; Nizami, Naila; Fatima, Syeda Tehseen (Infectious Diseases Journal of Pakistan, 2023)
Background: Neonatal sepsis is a clinical syndrome with presence of both infection and systemic inflammatory response syndrome. Thrombocytopenia is a marker of neonatal sepsis. Present study was conducted to determine association of thrombocytopenia with any specific infection. Methods: A total of 120 neonates were included in this cross sectional study conducted in the neonatal intensive care unit (NICU) of the Children’s Hospital, Lahore from January to July 2015. All neonates with presumed sepsis and positive blood cultures were included. The neonates who had received platelet/ blood transfusion or drugs known to cause thrombocytopenia were excluded. Data on age, gender, platelet count, microbiological culture and clinical outcome was collected on a proforma. Statistical analysis was performed using SPSS 20 to look for association between thrombocytopenia and different organisms (Gram positive, Gram negative or fungal) causing sepsis. Chisquare test and logistic regression methods were used for calculating significance. P-value of <0.05 was taken as significant. Results: A total of 120 newborns were included with 81 males (68%) and 39 females (32%). Their mean age was 140.28 hours (±130.71 SD). Thrombocytopenia was detected in 29% (n=35, p=0.90). Out of these septic & thrombocytopenic babies, Gram negative organisms were found in 69% (n = 24, p =0.31) and Gram positive organisms in 31% (n = 11, p=0.44). No case of fungal sepsis had thrombocytopenia. Considering the individual microorganism, only Klebsiella pneumoniae (p=0.027) had a significant association with thrombocytopenia. Conclusions: In neonatal sepsis, presence of thrombocytopenia may be an indicator of Klebsiella infection. Key words: Neonatal sepsis, thrombocytopenia, blood culture, microorganism